Evidence of Sasol Limited’s Contribution to Skills Development in Democratic South Africa - Mathekga, Jerry; Mahlaela, Audrey; Maciko, Loyiso (African Journal of Employee Relations, 2022)
There has been a renewed call nationally for the private sector to contribute to knowledge and skills development (i.e., capacity building) in South Africa. Yet, only a handful of writers have acknowledged the recent progress of Sasol Limited’s (hereafter Sasol or the company) contribution to knowledge and skills development in South Africa. Skills development is placed centrally as a means of empowering people to participate in the South African economy; to pursue alternative career opportunities; and to become self-employed. This article assesses a study that researched Sasol’s contribution to knowledge and skills development in South Africa. Sasol is a global integrated chemicals and energy company. The company was established in 1950 in Sasolburg, in the former Orange Free State (now Free State) province of South Africa, as a state-owned entity. The company was partially privatised in 1979 and wholly privatised in the early 2000s. The study aimed to explore Sasol’s skills development programmes. The information in the article was obtained from the company’s annual reports, as well as an interview with the company’s senior manager responsible for learning and development. The interview was conducted on 11 October 2021. The findings indicated that Sasol’s skills development is linked to the development agenda of the South African government and its key policies, notably, the National Development Plan 2030 (NDP); the Medium-Term Strategic Framework 2019–2024 (MTSF); the White Paper on Science, Technology and Innovation (WPSTI); and the Industrial Policy Action Plan 2018/19–2020/21 (IPAP). Further, Sasol contributes to women’s empowerment in South Africa through its skills development programme.